Music, drama, and social development in Portuguese children - Boal-Palheiros, Graça; Ilari, Beatriz (Frontiers in Psychology, 2023)
Social competence plays a fundamental role in children’s development, and in their functioning at school and in life. Social skills, as learned behaviors that allow children to positively interact with others, are important for success in both academic and peer-group settings. Children’s participation in collective music and other arts education has been associated with the development of social skills. However, different measures and diverse programs adopted in various studies make it difficult to contrast study findings. Additionally, research with children from low-income families remains scarce. The aim of this study was to examine the role of music and drama education programs in primary schools on the development of social skills of Portuguese children from disadvantaged communities. Both programs were carefully designed with performing, creating, and listening activities, and were delivered by specialist and experienced teachers/performers, who used active and participatory teaching strategies. In our longitudinal design with pre- and post-evaluations, we used the Social Skills Rating System or SSRS - Teacher Form, adapted for the Portuguese population. Classroom teachers rated their students’ social skills on a 3-point scale in three domains: Social skills (Cooperation, Assertion, Self-control), Behavioral problems (Externalizing problems, Internalizing problems, Hyperactivity) and, on a 5-point scale, Academic competence. Our findings suggest that participation in music and drama programs during one school year improved children’s assertion and self-control, and cooperation in the drama group. Participation in the music and drama programs also appeared to serve as a protective factor by reducing externalizing, internalizing and behavioral problems. These findings are discussed in light of previous studies along with limitations and directions for future research.